Multiculturalism Pesantren: Photographing Peace Education-Based Islamic Education Management Strategy in Pesantren Ngalah, Pasuruan, East Java - Mukhammad Abdullah (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2021)
This research discusses exciting things that are relevant to the development of science. Peace-education management with a set goal of creating a peace-building community becomes the main goal in the curriculum. This study took the setting located in the Islamic educational institution Pesantren Ngalah, Pasuruan East Java, as a pilot pattern of formulation and actualization of Islamic education management based on religious conflict resolution. This research is qualitative by translating field research phenomena approached with a descriptive-analysis approach. Data was excavated by triangulation; Documentation, interviews, and observations. After going through the analysis test has Miles & Huberman and examined the validity of technical triangulation data, researcher found the results of the research. Multiculturalism education strategies and efforts to prevent religious conflicts from creating religious harmony in Pesantren Ngalah conducted through planting the values of pluralism, tolerance, inclusive and humanistic hidden curriculum; imitate the attitude (attitude) and mindset of the leader of Pesantren Ngalah; apply the value of pluralism through the competence of scholarly output; and all elements work together to create social harmony. The results of peace education analysis concluded that the pattern of creation of religious harmony. The orientation of religious, social harmony with hidden peace education, both in the form of hidden mindset, hidden culture, and social hidden. Pesantren Ngalah uses the value of peace education free of multiculturalism values as a curriculum guideline. The development of a pluralism mindset and the power of reducing religious conflict combed in the human subconscious.